2020
DOI: 10.3390/bios10090120
|View full text |Cite
|
Sign up to set email alerts
|

LipiSensors: Exploiting Lipid Nanoemulsions to Fabricate Ionophore-Based Nanosensors

Abstract: Ionophore-based nanosensors (IBNS) are tools that enable quantification of analytes in complex chemical and biological systems. IBNS methodology is adopted from that of bulk optodes where an ion exchange event is converted to a change in optical output. While valuable, an important aspect for application is the ability to intentionally tune their size with simple approaches, and ensure that they contain compounds safe for application. Lipidots are a platform of size tunable lipid nanoemulsions with a hydrophob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…However, this change in material properties is not a concern for the sensing mechanism, as other work has already demonstrated that for this class of sensors, the structural nanoparticle matrix is easily adaptable to other materials assuming the hydrophobicity remains similar, a result extended in this work. 14 , 18 , 39 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this change in material properties is not a concern for the sensing mechanism, as other work has already demonstrated that for this class of sensors, the structural nanoparticle matrix is easily adaptable to other materials assuming the hydrophobicity remains similar, a result extended in this work. 14 , 18 , 39 …”
Section: Resultsmentioning
confidence: 99%
“… 16 However, the current fabrication approach for nanosensors is reliant on emulsification solvent evaporation (ESE)—yielding minimal nanoparticle size control, large polydispersity, and poor options to select specific nanoparticle sizes while retaining sensor function. 17 While some alternate approaches with different materials have shown some limited size tuning, 18 the current approaches do not offer the control over nanoparticle fabrication seen with FNP.…”
mentioning
confidence: 99%
“…Ionophore-based ionselective electrodes and optodes have been widely recognized because of the high selectivity, versatility, and robustness [8][9][10][11][12][13]. Recently, several research groups are interested in developing the nanoscale ion-selective optodes in the form of various nanoparticles [11,[14][15][16][17][18]. The nano-optodes could share a similar sensing mechanism with polymer film-based bulk optodes where an increase of K + concentration ([K + ]) leads to the deprotonation of a pH indicator (H + chromoionophore) in the nanospheres [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…19 Moreover, stable in solution cubosomes/hexosomes are obtained in a simple process. Surprisingly, lipid nanostructures were not of interest as ion-selective sensor matrices before 20,21 although biosensing with these systems has been considered. 22 From the point of view of ion-sensing, the additional advantage has the possibility of adjusting the internal arrangement of channels by a temperature trigger, affecting accessibility of the bulk probe for the analyte and ultimately controlling the response pattern of the sensor.…”
mentioning
confidence: 99%
“…Moreover, stable in solution cubosomes/hexosomes are obtained in a simple process. Surprisingly, lipid nanostructures were not of interest as ion-selective sensor matrices before , although biosensing with these systems has been considered …”
mentioning
confidence: 99%